CSA-based harmonic elimination controlled reduced switch multilevel inverter for standalone PV system - Sen, Priyanka; Sahoo, Ashwin Kumar; Jha, Vandana (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
A standalone photovoltaic (PV) system has emerged as a clean energy solution for application in remote areas. To establish such a system a suitable converter is required for voltage boosting as well as to produce high-quality output as required by the load. To achieve this, multilevel inverters (MLIs) are the proven substitute in PV systems. A conventional MLI uses multiple sources and switches that increase the cost and complexity. To provide a complete stand-alone system solution that addresses this issue, reduced component switched capacitor (SC) based seven-level MLI is disclosed in this paper. A new crow search algorithm (CSA) based selective harmonic elimination (SHE) method is employed to estimate the switching angles. The dominant harmonic orders are removed from the 7-level SC-MLI output while the desired firing angles for the switches are evaluated. Using only seven switches, the circuit boosts the voltage to 1.5 times with the aid of self-balanced capacitors. Therefore, the circuit does not require an additional control circuit for voltage balancing. The overall system is designed in MATLAB/Simulink environment to test under different operating conditions. An experimental prototype of the 7-level SCMLI is also designed to validate the CSA-based SHE control and MLI performance in real time.